A Case Study to Determine if Micro-Unit Developments Create Another Step Along the Housing Ladder for Low-Income Homeowners in Soweto - van Eeden, Marile (Department of Construction Economics and Management, 2023)
The South African government has been providing subsidised housing for decades, yet a large portion of the population live in inadequate housing. More recently, it has been found that many residents earn more than what is allowed to qualify for a housing subsidy; however, they earn too little to enter the formal market. These residents, therefore, turn to the informal market, where they obtain housing in informal settlements or housing in backyards. A new housing development trend is emerging in the form of backyard micro-unit developments. This research proposal examines the potential of backyard micro-unit development to address the low-income housing demand and how these developments can be used as a means to climb the housing ladder. An exploratory case study is undertaken to understand housing trends within Soweto, South Africa. A mixed research approach was used together with both quantitative and qualitative data. The COVID-19 pandemic, however, posed a significant limitation on fieldwork; therefore, the study relied on secondary data sources. The analysis indicates that the backyard micro-unit developments mimic the formal market, and the backyard micro-unit developments provide an adequate housing option for low-income earners. Furthermore, the demand for affordable accommodation results in the commercialisation of the informal rental market and presents the opportunity for homeowners to move up the housing ladder, and it addresses the mounting housing backlog in Soweto. Furthermore, the analysis indicates the significance of a title deed for residents in townships and its role in their ability to climb the housing ladder.